Effectiveness of open-ended learning method in fluid mechanics laboratory course - Fadhil S.S.A.B.; Jalal M.F.B.A.; Anuar N.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education; Fluid mechanics; Laboratories; Learning systems; Students; Collaborative learning; Communication skills; Laboratory course; Learning methods; Mechanics laboratory; Open-ended; Traditional learning; Engineering education